Survey of Administrative Health Status from the Point of View of Health Workers in Teaching Hospitals in Isfahan - Haniye Sadat Sajadi; Farshad Halaji; Naser Marouf (Kerman University of Medical Sciences, 2015)
Introduction: The administrative health improvement is one of the administrative reform's priorities in our health care organizations, Being aware of the current status of administrative health is necessary to propose the strategies of administrative health improvement. This study aimed to determine the administration health status of teaching hospitals and contribute to improve the it. Method: This cross-sectional and analytical-descriptive study was conducted in 11 teaching hospitals of Isfahan city in 2014. 555 of clinical and non-clinical staff were selected using simple stratified sampling method and completed the questionnaire. The data collection tool was a researcher-made questionnaire the validity and reliability of which were tested. The questionnaire was designed in two parts. The first part included 9 close ended questions about demographic information, and the second part contained 24 close ended questions related to the administrative health status with 5-item Likert scale. Collected data of 391 completed questionnaires were analyzed using SPSS software (version 16), t-test, and Analysis of Variance. Results: More than half of respondents were female (56.53%) and the rest were male. Over 76/47% of participants were married. The mean score of administrative health from the view of employees was 2.11 (less than average). The most important threatening factors of the administrative health were lack of sense of commitment of employees (1.00), the lack of effective violations reporting (1.00), and information manipulating and disclosing. Females, younger than 25, MD degree and single respondents viewed the administrative health status better than others. Conclusion: Regarding the necessity of administrative health improvement, taking actions such as strategies to increase the employees' commitment, the establishment of an efficient comprehensive system of accountability and reporting, and informing about the importance of valid information and broadcasting them are recommended to reach better administrative health status. Keywords: Administrative Health, Clinical Staff, Non Clinical Staff, Teaching Hospital, Isfahan City. Citation: Sajadi HS, Halaji F, Marouf N. Survey of Administrative Health Status from the Point of View of Health Workers in Teaching Hospitals in Isfahan. Journal of Health Based Research 2015 1(2):123-132.